Bringing Research Into Practice: An Evaluation of Michigan's Sexual Assault Kit. (May 2016) - Shaw, Jessica; Campbell, Rebecca; Hagstrom, Julie; O'Reilly, Leslie; Kreiger, Gail; Cain, Debi; Nye, Jeff
The importance of research-informed practice for the field of sexual assault has been stressed by academics and practitioners alike. However, there are few examples of researcher–practitioner partnerships in the literature, therefore providing minimal guidance for this process. This article describes a researcher–practitioner partnership that was successful in using evaluation data to guide practice and policy decisions regarding the development and implementation of a new sexual assault kit for the state of Michigan. Cousins's practical participatory evaluation theory was used as the guiding framework for the evaluation. Data collection methods included focus groups with practitioners from five, regionally dispersed health care settings in Michigan, and surveys with forensic scientists throughout the state's regional laboratory system. This case study highlights how researchers and practitioners worked together for data collection, analysis, and dissemination to support research-informed practice in this state. Lessons learned and future recommendations for forming researcher–practitioner partnerships to improve the response to sexual assault are discussed 1 .